1998
DOI: 10.1080/02841859809172455
|View full text |Cite
|
Sign up to set email alerts
|

Measuring anteversion in the femoral neck from routine radiographs

Abstract: FNA measurement can be made from a routine radiographic examination of the hip and a lateral view of the knee. This method achieves an acceptable level of accuracy and reproducibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 16 publications
2
8
0
Order By: Relevance
“…Pre-operative calculations of femoral torsion, version and offset as well as acetabular version and inclination have been previously undertaken using plain radiographs [5,6], and subsequently more accurately using CT scanning [7]. The use of CT guidance in the placement of prostheses has been shown to significantly improve the post-operative component positions compared with freehand techniques [8].…”
Section: Introductionmentioning
confidence: 99%
“…Pre-operative calculations of femoral torsion, version and offset as well as acetabular version and inclination have been previously undertaken using plain radiographs [5,6], and subsequently more accurately using CT scanning [7]. The use of CT guidance in the placement of prostheses has been shown to significantly improve the post-operative component positions compared with freehand techniques [8].…”
Section: Introductionmentioning
confidence: 99%
“…Then, we calculated the stem anteversion (θ) using the formula by Ogata and Goldsand. [26] In brief, α = 180°-neck-shaft angle on AP view. β = 180°-radiological anteversion of the stem on translateral decubtus view.…”
Section: Calculation Of Real Stem Anteversion From Radiological Stem mentioning
confidence: 99%
“…Implant malposition is an important risk factor for dislocation after total hip replacement (THR) and accurate assessment of implant position is critical to determine whether to change the implant in dislocating THR. [1][2][3][4][5][6][7][8][9][10][11][12] Although computerized tomography (CT) scan is accurate in the measurement of the acetabular and femoral component position, it has definite limitation due to cost and risk of radiation hazard. [13][14][15][16] Several studies reported radiological methods to measure the abduction and version of the acetabular component using plain radiograph.…”
Section: Introductionmentioning
confidence: 99%
“…Egund and Palmer [1] describe a method which consists of acquiring several CT slices at selected locations, manually extracting geometric features from those slices, defining a reference plane and a plane though the femur head from the features, and measuring anteversion as the angle between the plane normals. Herman and Egund [3] propose to measure anteversion from three CT slices and from fluoroscopic images of the whole femur at precise predetermined viewpoints. The method requires significant manual user intervention.…”
Section: Previous Workmentioning
confidence: 99%